A Date Which Will Live : Pearl Harbor in American Memory - Rosenberg, Emily S., 1944- (Book collections on Project MUSE., 2003)
"Emily S. Rosenberg considers the emergence of Pearl Harbor's symbolic role within multiple contexts: as a day of infamy that highlighted the need for future U.S. military preparedness, as an attack that opened a "back door" to U.S. involvement in World War II, as an event of national commemoration, and as a central metaphor in American-Japanese relations. She explores the cultural background that contributed to Pearl Harbor's resurgence in American memory after the fiftieth anniversary of the attack in 1991. In doing so, she discusses the recent "memory boom" in American culture; the movement to exonerate the military commanders at Pearl Harbor, Admiral Husband Kimmel and General Walter Short; the political mobilization of various groups during the culture and history "wars" of the 1990s and the spectacle surrounding the movie Pearl Harbor. Rosenberg concludes with a look at the uses of Pearl Habor as a historical frame for understanding the events of September 11, 2001"--Jacket